The impact of social capital to improve rural households’ resilience against flooding: evidence from Iran - Savari, Moslem; Jafari, Ahmad; Sheheytavi, Abbas (Frontiers in Water, 2024)
Floods have significantly affected many regions worldwide, imposing economic, social, and psychological consequences on human societies, in recent decades. Rural communities in Iran are particularly vulnerable to floods, and without effective risk reduction systems, the impact can be exacerbated. In this context, this study aims to investigate the role of social capital in enhancing the resilience of rural households against floods in the southwest of Iran. The statistical population includes all rural households in Shushtar County that have experienced floods at least once. The primary tool for data collection was a questionnaire and obtained data were analyzed using structural equation modeling. In examining the situation of confrontation between different groups of people based on the state of social capital and resilience, it can be said that men, older people and people with higher income had more resilience and social capital to deal with floods. In addition, the results revealed that components of social capital (social networks, social solidarity, social trust, social awareness, participation and collection action) explained 68.1% of the variance in the resilience of rural households against floods. Overall, our findings can provide new insights for policymakers in the area, contributing to the reduction of flood impacts and promoting safer living conditions in flood-prone areas.